Development of PBL-Based LKPD on the Topic of the Circulatory System Humans for Class VIII Students - Laras Prasetyo; Indra Fardhani; Erti Hamimi (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2024)
Learning objectives can be achieved if students are diligent in learning activities. Student activeness can be assessed through their involvement in study groups, responsibility, and how they express their opinions. Therefore, problem-based learning materials are necessary to train students' thinking skills and to ensure they are active in learning activities. The aim of this research is to develop a student worksheet product based on problem-based learning on the human circulatory system material, to test the product's validity, and to assess the product's practicality. The mechanism used in this research is Research and Development (R&D). Data collection involved respondents from 8th-grade students (n = 130) and science subject teachers (n = 6) for practitioner validation and readability tests. The scope of this research is limited to the feasibility assessment of the Problem-Based Learning student worksheet by material experts, media experts, practitioners, and student readability tests. The teaching materials developed by the researchers include factual problems in daily activities, making them easy for students to understand and supported by videos and articles to comprehend the material. Data analysis shows that (1) the assessment criteria by material experts indicate a valid category with an average of 80.83%; (2) it is considered very valid as evidenced by an average of 90% for media expert assessments; (3) student responses to the worksheet are very good with an average of 95.37%; (4) based on practitioner expert tests, it is stated to be very valid with an average of 94.7%.